Cerebrovascular diseases in the critically ill - Krieger, Derk; Hacke, Werner (Current opinion in critical care, 1997)
Recent advances and perspectives in monitoring and selecting critically ill patients with cerebrovascular disease for specific treatment alternatives are reviewed. Current management for intracranial hypertension and respiratory failure in patients with severe strokes are disputed and the relationship of blood pressure, cerebral blood flow, and metabolism for cerebral ischemia is discussed. Furthermore, advances in techniques to continuously monitor brain tissue metabolism and new therapeutic approaches to ameliorate effects of cerebrocascular catastrophies are analyzed.